Frictional flow characteristics of microconvective flow for variable fluid properties. (24th September 2015) - Kumar, Rajan; Mahulikar, Shripad P
Abstract: The present work investigates the frictional flow characteristics of water flowing through a circular microchannel with variable fluid properties. The computational analysis reveals the importance of physical mechanisms due to variations in thermophysical fluid properties such as viscosity μ ( T ), thermal conductivity k ( T ) and density ρ ( T ) and also their contribution in the characteristics of frictional flow. Various combinations of thermophysical fluid properties have been used to find their effects on fluid friction. It is observed that the fluid friction attains the maximum value in the vicinity of the inlet and diminishes along the flow. The main reasons are attributed to this, (1) near the inlet, there is a flow un development (the reverse process of flow development) due to μ ( T ) variation. (2) The viscosity of the water decreases with increasing temperature, which reduces fluid friction along the flow. It is noted that the skin friction coefficient ( c f ) reduces with increasing fluid mean velocity for a same value of constant wall heat flux ( In the vicinity of the inlet, the deviation of Poiseuille number ( Po ) from 64 (constant properties solution) is also investigated in this paper. Additionally, the relationship between Reynolds number ( Re ) and c f, Po and Re have been proposed for different combinations of thermophysical fluid properties. This investigation also shows that the effect of fluid property variations on pressure drop is highly significant for microconvective water flow.